E-cigarette or Vaping product use Associated Lung Injury (EVALI) in a 15 year old female patient - case report - Chiara Casamento Tumeo; Alessandra Schiavino; Maria Giovanna Paglietti; Francesca Petreschi; Alessandra Ottavianelli; Alessandro Onofri; Claudio Cherchi; Paolo Tomà; Renato Cutrera (BMC, 2022)
Abstract Background E-cigarettes are devices which allow to aerosolize liquids containing nicotine or other substances. Ever since they were released on the market in 2006, the number of users have been constantly increasing, especially among adolescents, ranging from 7,6% to 9,3% in the age group 18-24 years old from 2014 to 2019. Hand in hand with the spread of E-cigarettes many have been the efforts to understand their impact on health. EVALI (E-cigarette or Vaping product use Associated Lung Injury) is an emerging condition with a heterogeneous presentation with several reported cases worldwide. We mean to report a case of EVALI in a 15-year-old female Caucasian patient, who's currently attending her clinic follow-up at Bambino Gesù Pediatric Hospital in Rome. Case presentation The patient was admitted to the Emergency Room due to acute respiratory failure in November 2020. At admittance, she was severely dyspneic (HR 120 bpm, SatO2 75%). As she was hospitalized amid the COVID-19 pandemics, she underwent a nasopharyngeal swab for SARS-CoV2, which turned out negative, and a chest CT scan. Chest CT scan showed a central ground grass pattern with peripheral sparing. At the anamnestic recall, it was disclosed she was an e-cigarette smoker and occasional marijuana user. The microbiological work-up proved only positive for Rhinovirus. Her clinical and radiological case was discussed with our radiologist who suspected EVALI. She was assisted through HFNC, antibiotical therapy and corticosteroids with a dramatic recovery within the first 48 h. Conclusions EVALI started being recognized a specifically nosological entity in summer 2019, with increasing cases being reported. No diagnostic criteria have been agreed upon yet, but its usual presentation includes respiratory, gastrointestinal and systemic symptoms of different degree and the diagnosis can be hypothesised in case the patient has an evocative clinical and radiological presentation and has been an E-cigarette smoker in previous 90 days. Due to the novelty of the condition and its heterogeneous presentation it is of interest to report the cases in which EVALI is identified to raise awareness about this emerging new-age disease.